Parametric architectural design using shapes and structures - Manavis, Athanasios; Firtikiadis, Lazaros; Spahiu, Tatjana; Efkolidis, Nikolaos; Kyratsis, Panagiotis (Journal of Graphic Engineering and Design, 2022)
This paper explores the creation of architectural structures through parametric design tools. The proposed methodology presents an alternative framework of using digital tools for the product design development from the design thinking point of view. The main core of the suggested design process includes a great number of theoretical issues from design identity, design language and architectural design areas. As a result, designers can develop constructions for public spaces that are based on innovative morphologies by using new digital design techniques such as computational design (Rhino3D © and Grasshopper ©). The development of an architectural structure that aims to bring greenery into the city and increase the rest and action spaces is presented. A valuable aspect of this exploration is in positioning the proposed design framework inside - to aid in the creative process and better leverage downstream outcomes. The final steps of the proposed methodology include the production of the final architectural structure through rapid prototyping, laser cutting and engraving techniques. Article history: Received (November 26, 2021); Revised (May 5, 2022); Accepted (July 4, 2022); Published online (December 1, 2022)